Juridical Review of Legal Relations in Child Care Agreements (Study at The Orphanage Orphaned Daughter Aisyiyah Grogol Sukoharjo) - Septarina Budiwati; Ameilia Annisa Salsabila; Wardah Yuspin (Universitas Muhammadiyah Surakarta, 2022)
Along with the development of the era of human life, the birth rate of children is increasing rapidly. Children as creatures of God Almighty have the right to life and independence and to protection from parents, families, communities, and the state. The rapid development and increase in human civilization have an impact on the higher life of fulfilling services. In this case, the orphanage acts as a social welfare institution that has the responsibility of providing services to neglected children, as well as providing substitute services or child care in fulfilling their needs. Where this supports the birth of a child care agreement. One example is the child care agreement at the Aisyiyah Women's Orphanage Grogol Sukoharjo. The purpose of this study was to determine the form and content of the child care agreement at the Aisyiyah Grogol Sukoharjo Orphanage and to determine the legal relationship in the child care agreement at the Aisyiyah Grogol Sukoharjo Orphanage. The method used in this research is normative juridical method. The results showed that the form of the child care agreement at Aisyiyah Grogol Sukoharjo Orphanage is a written agreement and the contents of the agreement are also in accordance with Article 1338 of the Civil Code regarding the principle of freedom of contract and also in accordance with Article 1320 paragraph (1) of the Civil Code regarding the principle of consensualism. Furthermore, the legal relationship in this agreement is in accordance with Article 1338 paragraph (1) of the Civil Code regarding the principle of pacta sun servanda, in accordance with Article 1338 paragraph (2) and (3) of the Civil Code, and the rights and obligations arising in the agreement are in accordance with Law Number 4 of 1979 concerning Child Welfare and also QS Al Anam verse 151, Al Baqarah verse 233, At Tahrim verse 6.